Studying the effects of parenting acceptance and commitment therapy on mothers´ self- efficacy regarding children´ externalizing behavior problems - شیرین عظیمی فر; رضوان السادات جزایری; مریم السادات فاتحی زاده; احمد عابدی (فصلنامه خانواده پژوهی, 2018)
The aim of this study was to evaluate the effects of parenting acceptance and commitment therapy on parenting self- efficacy among mothers who have children with externalizing behavior problems. The research method was semi-experimental with pretest- posttest design and a control group. The research population was all mothers who have preschool children with externalizing behavior problems in Isfahan. The statistical sample included 30 mothers who were voluntarily selected regarding entrance criteria and randomly assigned into experimental and control group (each group included 15 subjects). Parenting acceptance and commitment therapy program was held for the experimental group during 10 sessions (each session lasted 90 minutes), while the control group received no intervention. The research instrument was parental self-agency measure (PSAM) that was conducted in pre-test, post-test and follow-up sessions for both groups. Descriptive statistics (mean & standard deviation) and inferential statistics were used to analyze the data. The results of the repeated measures variance analysis showed that parental self-efficacy has increased significantly in the experimental group compared to the control group. So it can be concluded that acceptance and commitment based interventions may increase parenting self -efficacy and lead to more satisfaction of parenting functions.